Rapid warming is associated with population decline among terrestrial birds and mammals globally. (22nd July 2018) - Spooner, Fiona E. B.; Pearson, Richard G.; Freeman, Robin
Abstract: Animal populations have undergone substantial declines in recent decades. These declines have occurred alongside rapid, human‐driven environmental change, including climate warming. An association between population declines and environmental change is well established, yet there has been relatively little analysis of the importance of the rates of climate warming and its interaction with conversion to anthropogenic land use in causing population declines. Here we present a global assessment of the impact of rapid climate warming and anthropogenic land use conversion on 987 populations of 481 species of terrestrial birds and mammals since 1950. We collated spatially referenced population trends of at least 5 years' duration from the Living Planet database and used mixed effects models to assess the association of these trends with observed rates of climate warming, rates of conversion to anthropogenic land use, body mass, and protected area coverage. We found that declines in population abundance for both birds and mammals are greater in areas where mean temperature has increased more rapidly, and that this effect is more pronounced for birds. However, we do not find a strong effect of conversion to anthropogenic land use, body mass, or protected area coverage. Our results identify a link between rapid warming and population declines, thus supporting the notion that rapid climate warming is a global threat to biodiversity. Abstract : Animal populations have undergone substantial declines in recent decades. These declines have occurred alongside rapid, human‐driven environmental change, including climate warming. Here we present a global assessment of the impact of rapid climate warming and anthropogenic land conversion on 987 populations of 481 species of terrestrial birds and mammals since 1950. We found that declines in population abundance for both birds and mammals are greater in areas where mean temperature has increased more rapidly. Our results identify a link between rapid warming and population declines, thus supporting the notion that rapid climate warming is a global threat to biodiversity.